Determinants of corporate social responsibility among farms in Russia and Kazakhstan: A multilevel approach using survey data - Anna Hajdu; Taras Gagalyuk; Eduard Bukin; Martin Petrick (International Food and Agribusiness Management Review, 2021)
Building on the institutional theory of corporate social responsibility (CSR) and research on CSR in the agriculture of post-Soviet transition economies, the present paper investigates the institutional, organizational and individual factors of farm engagement in CSR activities. Based on a survey of 800 farms in Russia and Kazakhstan, the interaction between the farms' social role and multilevel institutional characteristics is addressed. We observe notable positive effects of local labor sourcing, insecure land use conditions and farm size (in terms of land area) on farms' CSR engagement. Individually owned farms, as opposed to corporate farms, tend to be more CSR affine. In addition, we find weak statistical evidence of CSR engagement among the farms affiliated with agroholdings. We discuss the results in the context of different levels of CSR analysis.
Keywords: Q15; O130; Q130; M140; Q170; R110; 330; corporate social responsibility; primary agriculture; organizational-level factors; institutional-level factors; transition economies